PENDEKATAN SERVQUAL-LEAN SIX SIGMA MENGGUNAKAN DIAGRAM KONTROL T2 HOTELLING UNTUK MENINGKATKAN KUALITAS PELAYANAN PENDIDIKAN (Studi Kasus di Jurusan Statistika Universitas Diponegoro) - Darwati, Lulus; Mustafid, Mustafid; Suparti, Suparti (Jurnal Gaussian, 2015)
Measurement the service of quality has an important role in improving and evaluating the performance of a service process. Measuring the service of quality is not as easy as measuring the goods quality, because the assessment service is subjective. Therefore, ServQual dimension is used as a tool to measure the performance of service from the perspective of service’s users. Lean Six Sigma method is used to improve the performance of the services of quality that focused on the reduction of variations and the increasing of the speed of the process through the elimination of waste that occur in the flowing process. This research aims to implement the integration of ServQual and Lean Six Sigma method by controlling the process using Hotelling T2 control charts on the improvement of the quality of education services. The performance of the education services process overall is indicated by the value of the capabilities and the level of the sigma. The capability value amount 0.8407 and the level of sigma amount 2.748 indicates that the waste percentage in the process of educational services is about 10.6%. The waste of dominant on improving the quality of education services such as lecturer competencies, the status of departement accreditation, the speed in the administrative services, and the refinement of laboratory facilities especially the improvement on the computer facilities.Keywords : ServQual, Hotelling T2 control charts, Process Capability, Lean Six Sigma